2020
DOI: 10.3389/fnmol.2020.592644
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Mechanisms Driving Transthyretin Amyloidosis

Abstract: Transthyretin (TTR) amyloidoses are systemic diseases associated with TTR aggregation and extracellular deposition in tissues as amyloid. The most frequent and severe forms of the disease are hereditary and associated with amino acid substitutions in the protein due to single point mutations in the TTR gene (ATTRv amyloidosis). However, the wild type TTR (TTR wt) has an intrinsic amyloidogenic potential that, in particular altered physiologic conditions and aging, leads to TTR aggregation in people over 80 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 159 publications
0
23
0
Order By: Relevance
“…Among these molecules, natural flavonoids, such as EGCG, do not bind at the T4 binding site and stabilize the tetrameric structure by a stable interaction at the surface of each TTR monomer [ 28 ]. In particular, EGCG binds at the dimer–dimer interface, with a resulting effect similar to that of a cross-linker [ 41 ]. Our results indicate that OleA binds both at the main funnel and at the hydrophobic surfaces of TTR.…”
Section: Discussionmentioning
confidence: 99%
“…Among these molecules, natural flavonoids, such as EGCG, do not bind at the T4 binding site and stabilize the tetrameric structure by a stable interaction at the surface of each TTR monomer [ 28 ]. In particular, EGCG binds at the dimer–dimer interface, with a resulting effect similar to that of a cross-linker [ 41 ]. Our results indicate that OleA binds both at the main funnel and at the hydrophobic surfaces of TTR.…”
Section: Discussionmentioning
confidence: 99%
“…In amyloidosis, the aggregation of the major causative protein is promoted on the surface of the EV membrane, which is assumed to alleviate the pathological conditions ( Yuyama et al, 2012 ; Falker et al, 2016 ). TTR variant, as a major causative protein, causes TTR aggregation and deposition on specific tissues ( Bezerra et al, 2020 ). In this study, we showed via atomic force microscopy that TTR aggregation is promoted by EVs and that TTR multimerizes on the surface of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, advancements have been made in understanding the structural features of non-native and misfolded monomeric, oligomeric, and aggregated TTR species, employing various interdisciplinary techniques, such as solution/solid-state NMR spectroscopy, force spectroscopy, mass spectrometry, cryo-EM, and computational modeling. In particular, the proteolysis-induced amyloidosis mechanism of TTR has attracted much attention in recent years, and various structural studies have revealed the mechanistic details of this amyloidosis process [ 95 ]. Along with recent boosts in multidisciplinary methodology developments, further improvements are soon expected in understanding of TTR amyloidosis pathology and developing an even more effective therapeutic strategy against this disease.…”
Section: Discussionmentioning
confidence: 99%